Paramater Prestasi Kerja Dalam Perspektif Islam - Azuar Juliandi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Performance appraisal in the view of Islam has not been much studied by Islamic scholars, particularly who focused on the areas of management. During the time, performance parameters of the discourse in the literature of human resource management was the conventional view. The views of conventional, not necessarily in accordance with Islamic values. Most conventional literature suggests about the values of performance only oriented to the life of the world and the material itself, not for the purpose of the afterlife and spirituality. Based on the above issues, this paper aims to identify how the parameters of performance appraisal according to the Islamic view. The results of the analysis have attempted to explore the performance values in the Islamic perspective, based on the views of Muslim scholars who focused on the areas of human resource management. View of Islamic scholars also referenced from the Quran as the supreme reference source in Islam.